PENGARUH KOMPENSASI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN SWALAYAN LUWES NUSUKAN SURAKARTA - Novi Lifia; Alwi Suddin; Retno Susanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
A company always have a lot ways to solve their problem for their employes especially at Luwes Nusukan Supermarket Surakarta the goals are for good impact and for the neatly of the company for the future to reach vision and mision. there are some factors that can influence the employe's performance: compensation, motivation and work environment. the purpose of this research are for: (1) analysis the significant compensation influence to the employes performance, (2) analysis the significant motivation influence to the employes performance, (3) to analysis the significant work environment influence to the employe performance. This research is done with survey method at Luwes Nusukan Supermarket Surakarta. this research is using qulitatif and quantitatif data, the source is using premier and sekunder data. the population of this research are the employes of Luwes Nusukan Supermarket Surakarta that is contain with 70 employes. the sample of the research are 70 employes with using sensus method. the data collection is using quisioner. technique analysis data is using classic asumtion, multiple linear aggresion analysis, desctiptive analysis, t test, f test, and coeficient of determation test. The result is showing that the compensation is have a good impact and not significant with the employes performance, the motivation is have a good impact and significant with the employes performance, the environment also have a good impact and significant to the employes performance.